Private women, public meals social conflict in the synoptic tradition - Corley, Kathleen E. 1960- (Peabody, MA Hendrickson, 1993)
Includes bibliographical references and indexes.
Keywords: Dinners and dining in the Bible; Women in the Bible; Social conflict in the Bible; Bible. N.T. synoptic gospels -- criticism, interpretation, etc